Pembelajaran dengan Media Gambar untuk Meningkatkan Kemampuan Bersosialisasi Anak Usia Dini - Ayu, Aida Mustika; Mukri, Rusdiono; Aziz, M. Taufiq (At-Tadris: Journal of Islamic Education, 2022)
This study aims to determine learning with image media to improve early childhood social skills in class B in Raudhatul Athfal (RA) Albadariyah, Cimanggu 2 Village, Cibungbulang District, Bogor Regency. The research uses varied and interesting image media so that it can motivate children's interest. This type of research is collaborative classroom action research using Kurt Lewin's model. Each cycle consists of four stages, namely planning, implementing, observing, and reflecting. The research subjects were nine children of Group B RA Albadariyah. While the object of this research is the application of image media to improve children's social skills. Technique of data collection uses observation, documentation, and interviews. Data analysis uses qualitative descriptive techniques and quantitative approaches. The indicator of success in this study is when the average social ability of children through picture media has reached 80%. The results of this study indicate an increase in children's social skills through image media. This is evidenced by an increase in the average social ability of children in pre-action by 55.5%, increasing to 63.8% in Cycle I, and reaching 94.4% in Cycle II.